Sensibilidade de três variedades de cana-de-açúcar (Saccharum spp.) ao alumínio em solução avaliada por corantes indicadores - Malvestiti, Jacqueline Aparecida (Universidade Federal de São Carlos, 2011)
Brazil is the world's largest producer of sugarcane (Saccharum spp.). Its production is expanding in regions characterized by soils with low fertility and high acidity. The influence of Al toxicity on the development of the root system and on the interference of nutrient uptake has been presented as one of the main causes of the low productivity of many soils. The objectives of this study were: to evaluate the root development of sugarcane varieties RB855156, SP81 3250, and RB935744 in nutrient solution with different Al stress conditions (0, 70, 130, 380, 800, 1400, and 2000 μmol L-1); to examine morphological changes in sugarcane roots through optical microscopy; to verify the penetration of Al into the root tissue with the use of Al-complexing dyes; to test the efficiency of hematoxylin and pyrocatechol violet dyes as indicators of the presence of Al in root tissue. The experiment was conducted under laboratory conditions, in a completely randomized design, with four replications. The root growth rate results (cm day-1) were submitted to analysis of variance and compared by Tukey's test, at a 5% significance level. Morphological parameters of Al in root tissues, indicated by color, were explored in the form of images by photographic recording of observations under an optical microscope. Increasing the Al concentration in solution caused a decrease in the root elongation rate. The critical concentration of Al in solution, regardless of variety, according to statistical analysis was 1400 mmol Al L-1. The main morphological alterations of the roots were observed from the critical concentration of 800 mmol Al L-1 in solution, and include the production of callose and the collapse and deformation of the root cap. The hematoxylin dye was more efficient than pyrocatechol violet to indicate the accumulation and location of Al in the root tissue. The tolerance sequence of sugarcane varieties to Al in solution was RB935744 (late)>SP81-3250 (medium)>RB855156 (early), and this may be correlated with the cycle of the varieties.
Sensitivity of three sugarcane varieties (Saccharum spp.) to aluminum in solution evaluated by indicator dyes
Keywords: Cana-de-açúcar; Fitotoxidez; Ambientes de produção; Alumínio; Sugarcane; Aluminum; Al phytotoxicity; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO